A survey on information needs and search methods of Politeknik Kota Bharu senior officers / Mohamad Azwar Junoh - Junoh, Mohamad Azwar (2003)
The rapid development of ICT in Malaysia creates phenomena to majority of its community. For the higher education sector, implications include access to information from outside the library or information centers and a more towards end-user and away from mediated searches. Senior management should realize that their organizations are to survive in this dynamic era. Decisions have to be made concerning new educational opportunities, technical development; etc. This survey is to an insight into the information needs of, and information provision to Senior Officers of Politeknik Kata Bharu, Kelantan. The purpose of this study is to gather information on their problems, views, opinions and experiences, regarding their information needs and search methods. The changing and turbulent information environment requires for continual research and survey to ensure the needs of their information and search methods are satisfactory met.